(untitled) - Irving, Washington (New York, NY, 1991)
This story collections of great urbanity and poise from the first American author to burst onto the international literary scene. "The Alhambra," Irving's "Spanish Sketchbook," was inspired by his 1829 residence at the ancient Moorish palace at Granada; weaving history, legend, and description, it remains the best guidebook to this haunting place. Over 120 tales in all.
Keywords: American literature; 19th century